ANALISIS PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA RSUD DR. DJASAMEN SARAGIH KOTA PEMATANGSIANTAR - Geby Citra Ananda; Daud Arifin (Jurnal Abdi Ilmu, 2021)
The purpose of this study is to analyze the influence of leadership on employee performance, analyze the effect of compensation on employee performance, analyze the effect and compensation together on the performance of RSUD dr. Djasamen Saragih Pematangsiantar City. The population in this study were employees of RSUD dr. Djasamen Saragih in Pematangsiantar City in 2020 as many as 151 people. The samples of this study were 97 people. The sampling technique used a heterogeneous random sample method where data were obtained directly from the main source and obtained from the employees of RSUD dr. Djasamen Saragih, Pematang Siantar City in 2020. The hypothesis testing tool uses SPSS 22 software. From the results of the regression test, it was found that the compensation variable (X2) had the largest beta value, namely 0.483 with a significance of 0.000, followed by the leadership variable (X1) with a beta value of 0.227 and a significance of 0.009. The value of R Square shows a value of 0.347 or 34.70%, it can be interpreted that 34.70% of employee performance in RSUD dr. Djasamen Saragih Pematangsiantar City can be explained by leadership and compensation variables, 65.30% is explained by other variables. The conclusion is that achievement is influenced by leadership and compensation. The most influential factor on employee performance is compensation.